Requirement for acidic amino acid residues immediately N-terminal to the conserved domain of Saccharomyces cerevisiae TFIID. - Zhou, Q A (1991)
TFIID binds to TATA boxes and initiates the assembly of general transcription factors and pol II on promoters. TFIID proteins from various species consist of a highly conserved carboxy terminal domain and very divergent amino terminal domains. We investigated the function of the non-conserved amino terminal domain (residues 1-60) of Saccharomyces cerevisiae TFIID (YIID, 240 residues) by testing the ability of a series of YIID amino terminal deletion mutants to complement a YIID deficient yeast strain. Mutants with deletions up to amino acid 48 restored the YIID deficient yeast strain to an apparently wild type phenotype. However, deletion up to position 57 or 60 produced yeast strains which formed extremely small colonies. Moreover, overexpression of YIID delta 2-57 or YIID delta 3-60 protein in the presence of wild type YIID resulted in a dominant-negative inhibition of growth. No difference between the basal transcriptional activity of wild type YIID and these amino terminal deletion mutants was observed in vitro. However, transcriptional activation in vivo of promoter-lacZ fusions showed that the YIID delta 2-57 deletion affects the ability of certain promoters (CUP1 and an HSP UAS-CYC1 promoter hybrid promoter) to respond to upstream factor stimulation. At least one inducible promoter, PHO5, was not affected by this deletion. The defect produced by YIID delta 2-57 was due to the deletion of several acidic residues present between residues 48 and 57. The results show that the conserved carboxy terminal domain of YIID is sufficient for cell viability. However, an acidic region just amino terminal to the conserved domain is required for normal growth and transcription control in most yeast strains.